An interpretive analysis of the experiences of adults working as university support staff - Zini, Thembela Nomonde (Rhodes University, Faculty of Humanities, Department of Psychology)
Work means different things to different people and the different meanings they make of their work has the unique ability of contributing to a sense of identity. Support staff have to negotiate their personal identities and social identities to develop a work identity in the complex South African context that has its unique challenges. Exploring how support staff make sense of their experiences, when it comes to their identities, reveals what identity work strategies they use. An interpretative phenomenological method of inquiry was employed as an initial research method to explore the aspects that impact on the identity formation of support staff at Rhodes University. The study aims to investigate how support staff have constructed a work identity through their constructions of their experiences. Six participants were recruited through a purposive sampling method and data were collected using semi-structured interviews. The study revealed that support staff use the following identity work strategies to negotiate their identities: Financial, Personality, Career mobility, Roles, Status and Esteem, Subjective wellbeing. These themes were derived from the narratives of the participants, using the emphases in the data and suggest that support staff use identity work strategies both outside and within the workplace, when constructing their work identities. The study illustrates that as people ascribe different meanings to work, they will define and negotiate their identities in the workplace based upon those meanings. Identity work is indeed challenging for support staff because they need to use identity strategies that are enhancing to their self-esteem. Identity work is a challenging task because of the many tensions and demands of modern society, as adults negotiate their needs to provide for families and to find ways to construct their job status in positive ways.
Keywords: Universities and colleges -- South Africa; Universities and colleges Employees; Universities and colleges Sociological aspects; Identity (Psychology); Identity (Psychology) Social aspects; Work Psychological aspects; Work Social aspects; Interpretive Phenomenological Analysis (IPA)